Mode of Delivery in Drug-Dependent Pregnant Women: A Case Control Study - Ana Raquel Neves; Fabiane Neves; Isabel Santos Silva; Maria do Céu Almeida; Pitorra Monteiro (Journal of Pregnancy)
Objective. To determine the contribution of drug use during pregnancy to the route of delivery. Methods. A case-control study was conducted at a hospital in Coimbra, Portugal, between 2001 and 2014. Drug-dependent pregnant women (n=236) were compared with a control group of low risk women (n=228) in terms of maternal characteristics, obstetric history, pregnancy complications, and labor details. Factors that influenced the mode of delivery were determined. Statistical analysis was performed with SPSS v. 23.0 (IBM Corp.). p values < 0.05 were considered statistically significant. Results. Drug-dependent women presented a lower rate of cesarean delivery (18.2 versus 28.9%, p=0.006). After adjusting for the factors that were significantly related to the mode of delivery, drug dependency influenced the rate of cesarean section (β=0.567; 95% CI = 0.328–0.980). Within the drug-dependent group, the mode of delivery was significantly related to previous cesarean or vaginal delivery (p=0.008 and p<0.001, resp.) and fetal presentation (p<0.001), but not with the type of drug, route of administration, or substitution maintenance therapy. Conclusions. The drug-dependent group presented a significantly higher rate of vaginal delivery. However, this was not associated with the behavioral factors analyzed. We hypothesize that other social and psychological factors might explain this difference.